Public control over the activities of the State Bureau of Investigation: A comparative analysis: El control público de las actividades de la Oficina Estatal de Investigación: Un análisis comparativo - GulakОlena; Halai , Andrii; Iarmolenko, Iuliia; Spodynskyi, Oleksandr; Kapitanenko, Nataliia (Political Questions, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*110.23px); top: calc(var(–scale-factor)*261.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.10096);" role="presentation">The purpose of this work was to analyze the adequate level of <span dir="ltr" style="left: calc(var(–scale-factor)*96.06px); top: calc(var(–scale-factor)*272.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14524);" role="presentation">legal support for the implementation of public control over the <span dir="ltr" style="left: calc(var(–scale-factor)*96.06px); top: calc(var(–scale-factor)*283.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11432);" role="presentation">activities of the State Investigation Bureau through the activities <span dir="ltr" style="left: calc(var(–scale-factor)*96.06px); top: calc(var(–scale-factor)*294.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12346);" role="presentation">of the Public Control Council. To achieve the objective, general <span dir="ltr" style="left: calc(var(–scale-factor)*96.06px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.07147);" role="presentation">scientific <span dir="ltr" style="left: calc(var(–scale-factor)*142.69px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15582);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*166.73px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08858);" role="presentation">special <span dir="ltr" style="left: calc(var(–scale-factor)*204.31px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.07147);" role="presentation">scientific <span dir="ltr" style="left: calc(var(–scale-factor)*250.94px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1319);" role="presentation">methods <span dir="ltr" style="left: calc(var(–scale-factor)*296.66px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03721);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*312.65px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09952);" role="presentation">cognition <span dir="ltr" style="left: calc(var(–scale-factor)*361.54px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08749);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12602);" role="presentation">used <span dir="ltr" style="left: calc(var(–scale-factor)*80.93px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11905);" role="presentation">simultaneously, <span dir="ltr" style="left: calc(var(–scale-factor)*157.21px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13625);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*172.47px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1357);" role="presentation">particular <span dir="ltr" style="left: calc(var(–scale-factor)*222.41px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08853);" role="presentation">dialectical, <span dir="ltr" style="left: calc(var(–scale-factor)*276.30px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08203);" role="presentation">logical- formal, <span dir="ltr" style="left: calc(var(–scale-factor)*347.33px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09683);" role="presentation">analysis <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*327.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.16074);" role="presentation">and synthesis, systemic-structural, legal-comparative, legal-formal and <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*338.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12745);" role="presentation">prognostic. On the basis of a comparative analysis of the legal regulation <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*349.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11995);" role="presentation">of the issues of formation and activity of the Public Control Councils in a <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*360.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11492);" role="presentation">number of newly created law enforcement bodies, a system of blocks was <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*371.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14497);" role="presentation">highlighted, which were the subject of analysis, namely: 1) control over <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*382.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14596);" role="presentation">the activity of the body; 2) powers of the Public Control Council; 3) the <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*393.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14937);" role="presentation">name of the main area of activity of the Public Council; 4) the object of <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*404.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12419);" role="presentation">approval of the Regulations of the Public Council. Everything allowed to <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*415.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12864);" role="presentation">conclude which are the «bad» normative constructions, the contradictory <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*426.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13193);" role="presentation">norms in the related normative acts and to locate the need for unification <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*437.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1014);" role="presentation">of approaches according to the identified structural blocks, which were the <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*448.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.10738);" role="presentation">object of analysis. In addition, attention is focused on those directions that <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*459.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.10407);" role="presentation">require further scientific analysis and regulatory optimization.